Interaction of Time-periodic Surface Modulation and Oscillatory Bio-convection in a Porous Medium - Kiran, Palle; Amarnath, M.; Narsimlu, G. (Discontinuity, Nonlinearity, and Complexity, 2026)
This work investigates the effects of thermal modulation on Darcy-Brinkman bio-convection in a porous medium saturated with a Newtonian fluid containing gyrotactic microorganisms. We investigate the oscillatory bioconvection with low modulation amplitude using a weak nonlinear stability analysis. The heat transfer is measured by the mean Nusselt number governed by a complex Ginzburg-Landau equation (CGLE). The CGLE is derived by solvability condition at lowest order of perturbed parameter. The results are presented graphically, illustrating the impact of the system parameters on heat transfer. The results show that both Vadaszs number and modulation amplitude have a progressive effect on heat transfer. On the other hand, upon increase in the modified bio-Rayleigh number and cell eccentricity leads to a decrease in heat transfer. It is found that only OPM/LBM are effective on controlling heat transfer than IPM. This highlights the effectiveness of external modulation in controlling heat transport within the system. Further, it is found that the convective heat transfer process may be delayed, due to asymmetries and irregularities (α eq 0) of microorganisms than spherical-shaped microorganisms (α = 0).